PENGUATAN KELEMBAGAAN TANI MELALUI IMPLEMENTASI VALUE CO-CREATION ANTARA PETANI DAN BANDAR PADA RANTAI PASOK SAYURAN DATARAN TINGGI DI JAWA BARAT (Suatu Kasus Di Kecamatan Ciwidey, Kabupaten Bandung) - rahmat prasetya (Politeknik Pembangunan Pertanian Bogor, 2018)
ABSTRACT Growth of vegetable agribusiness accompanied by an increase in the amount of vegetable consumption makes vegetables as a strategic commodity that has the opportunity to be developed, one of which is the production center in Bandung regency. However, there are still many problems in vegetable supply chain systems such as low and inconsistent product quality, long marketing chains, lack of transparency and inequity in the distribution of risk-profit among supply chain members causing inequality in the supply chain and causing powerlessness of small farmers. To improve the supply chain system of vegetables as well as to increase the empowerment of farmers, intervention through a series of workshops with value co-creation approach in two groups of farmers and vegetable farmers in Kecamatan Ciwidey in 2017 with the aim to access structured markets. This study aims to find out how the implementation of value co-creation between farmers and bandar with reference to the framework ADTR (Access, Dialogue, Transparency and Risk-Benefit) which is a modification of the DART value co-creation framework. The research design is done quantitatively by survey technique. Data analysis method used is descriptive statistical analysis to explain the condition that occurred in the field based on interview result using questionnaire. The result of data analysis shows that the implementation of value co-creation between farmer and bandar has run well and fulfill the rules on the four dimensions of the ADTR framework with the highest value of the implementation of transparency, dialogue, information access and risk-benefit assessment. Keyword : value co-creation, vegetables supply chain, ADTR Framework, farmer, wholesaler ABSTRAK Perkembangan agribisnis sayuran yang disertai dengan peningkatan jumlah konsumsi sayuran menjadikan sayuran sebagai komoditas strategis yang memilki peluang untuk dikembangkan, salah satunya di daerah sentra produksi di Kabupaten Bandung. Namun demikian masih banyak permasalahan dalam sistem rantai pasok sayuran seperti kualitas produk yang rendah dan tidak konsisten, rantai pemasaran yang panjang, kurangnya transparansi serta ketidakadilan pembagian risiko-keuntungan antar pelaku anggota rantai pasok sehingga menyebabkan ketimpangan pada rantai pasok serta menyebabkan ketidakberdayaan petani kecil. Untuk memperbaiki sistem rantai pasok sayuran sekaligus meningkatkan keberdayaan petaninya, dilakukan intervensi melalui serangkaian workshop dengan pendekatan value co-creation pada dua kelompok petani dan bandar sayuran di Kecamatan Ciwidey pada tahun 2017 dengan tujuan untuk mengakses pasar terstruktur. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi value co-creation antara petani dan bandar dengan mengacu pada framework ADTR (Access, Dialogue. Transparency and Risk-Benefit) yang merupakan modifikasi dari framework DART value co-creation. Desain peneltian dilakukan secara kuantitatif dengan teknik survei. Metode analisis data yang digunakan adalah analisis statistik deskriptif untuk menjelaskan kondisi yang terjadi di lapangan berdasarkan hasil wawancara menggunakan kuesioner. Hasil analisis data menunjukkan bahwa implementasi value co-creation antara petani dan bandar telah berjalan dengan baik dan memenuhi kaidah pada keempat dimensi framework ADTR dengan urutan nilai tertinggi yaitu implementasi transparansi, dialog, akses informasi dan penilaian risiko-manfaat. Kata kunci : Value co-creation, framework ADTR, rantai pasok sayuran, petani, bandar